Critical Success Factors Of Food Supplement Industry In Penang - Ling, Teh Hooi (2009)
Through this study, consumers could further understand the food supplement issues. Based on Penang consumer survey, this study sheds some lights how Penang consumer bahaviors are in taking food supplement, which covers factors that promoting food supplement intake and factors consumers take into consideration in consuming food supplement